2022
DOI: 10.47895/amp.vi0.6256
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of Physicians to Local Guideline Recommendations among Patients with COVID-19 in Two Tertiary Public Hospitals in Metro Manila, Philippines: A Rapid Assessment Study

Abstract: Objectives. Adherence to clinical practice guidelines (CPG) has been shown to reduce inter-physician practice variation and improve quality of care. This study evaluated guideline adherence of physicians in two tertiary public hospitals to local CPG on COVID-19.Methods. This was a multicenter, retrospective chart review, rapid assessment method study. Guideline adherence and non-adherence (overuse and underuse) to 15 strong recommendations in the prevailing Philippine COVID-19 Living Recommendations were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(19 reference statements)
0
0
1
Order By: Relevance
“…Although there was some evidence of change in treatment in the time immediately after a guidance update, clinical practice alignment with national guidelines was low across all treatment types. This finding is in contrast with other studies that have found that clinicians followed guidelines and treatment of hospitalized patients was generally responsive to changes in medical evidence and public policy over the course of the early phases of the pandemic ( 8 , 11 , 18 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Although there was some evidence of change in treatment in the time immediately after a guidance update, clinical practice alignment with national guidelines was low across all treatment types. This finding is in contrast with other studies that have found that clinicians followed guidelines and treatment of hospitalized patients was generally responsive to changes in medical evidence and public policy over the course of the early phases of the pandemic ( 8 , 11 , 18 ).…”
Section: Discussioncontrasting
confidence: 99%